Solitary Langerhans cell histiocytosis of frontal lobe: a case report and literature review - Cai, Shanshan; Zhang, Sheng; Liu, Xueyong; Lin, Yuanxiang; Wu, Chunlin; Chen, Yupeng; Hu, Jianping; Wang, Xingfu (Chinese Journal of Cancer Research; Vol 26, No 2 (April 26, 2014): Chinese Journal of Cancer Research, 2014)
The brain parenchymal Langerhans cell histiocytosis (LCH) without systemic disease or lytic skull lesions is extremely rare. We report a 23-year-old male presenting with new onset 1 hour seizure with loss of consciousness 20 days prior to admission, and recurrent seizure 2 weeks later. Brain magnetic resonance imaging (MRI) showed an irregularly mass with enhancement involving the right frontal lobe. Microscopically, the lesion was characterized by sheets of Langerhans cells in addition to reactive inflammatory elements. Immunohistochemically, Langerhans cells were positive for Langerin, CD1a and S-100 protein. The patient received no chemotherapy or radiotherapy after surgery. After 24 months of follow-up, no recurrence or other systemic lesions were observed. Although there is no standard treatment for solitary cerebral LCH, the prognosis generally appears to be good.